THE IMPORTANCE OF EXERCISE IN TEACHING LOGICAL PROBLEM SOLVING (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article discusses the methods of solving logical problems related to work and productivity included in elementary school mathematics textbooks. The article considers a demonstrative method of solving logical problems. The differences in working with similar problems in the upper grades and elementary grades are shown.